Chronic Cerebral Hypoperfusion Activates the Coagulation and Complement Cascades in Alzheimer's Disease Mice. (15th September 2019) - Shi, Xiaowen; Ohta, Yasuyuki; Liu, Xia; Shang, Jingwei; Morihara, Ryuta; Nakano, Yumiko; Feng, Tian; Huang, Yong; Sato, Kota; Takemoto, Mami; Hishikawa, Nozomi; Yamashita, Toru; et al.
Abstract: Alzheimer's disease (AD) in the elderly is frequently accompanied by chronic cerebral hypoperfusion (CCH), which impairs the clearance of amyloid beta (Aβ) due to the dysfunction of the blood–brain barrier (BBB) and accelerates the AD pathology. Since the coagulation and complement cascades are associated with BBB dysfunction and AD pathology, we investigated the expression changes of coagulation (fibrinogen alpha chain-FGA, coagulation factor XIII A chain-Factor XIIIα) and complement (plasma protease C1 inhibitor-C1-INH, Complement component 3-C3) factors in the brain of novel AD model (APP23) mice with CCH at 12 months of age. Immunohistochemical and immunofluorescent analysis showed that the expressions of FGA, Factor XIIIα, C1-INH and C3 were significantly increased in cerebral neocortex, hippocampus, and thalamus of APP23 + CCH group ( n  = 12) as compared with wild type (WT, n  = 10) and APP23 ( n  = 10) groups ( ⁎ P  < .05 and ⁎⁎ P  < .01 vs WT; # P  < .05 and ## P  < .01 vs APP23), especially near and inside of neurovascular unit. The present study suggests that CCH activated both the coagulation and complement cascades in a novel AD model mice brain accompanied by the acceleration of AD pathology. Highlights: Chronic cerebral hypoperfusion (CCH) accelerates the primary AD pathology. CCH exacerbated the expression of FGA and Factor XIIIα in the brain of AD mice. CCH significantly induced the expression of C1-INH and C3 in the brain of AD mice. These expressions increased especially near and inside of neurovascular unit.